Literasi Kebijakan Pengelolaan Dana desa di Desa - Sutikno, Bambang; Repiyanti, Repiyanti; Atmajaya, Andi; Fitri, Dasa; Sari, Dalima Permata (Universitas Dehasen Bengkulu, 2021)
This research is motivated by one way to realize good governance in the management of the Village Fund is to pay attention to the stages of management, planning, implementation, reporting, and accountability. In managing the government in a village, the village head needs assistance from villagers. These villagers work according to their duties. Because of its large role, it is necessary to formulate regulations or laws related to village government to regulate village government, in order to carry out its role as well as possible. In connection with this, the role of the community is also important, especially in the decision-making process and the implementation of activities related to the needs of village fund management.